Mosque: As Aplace to Educate Truth, Passionate and Beauty to The Society of Kawruh Pamomong Ki Ageng Suryomentaram in Yogyakarta - Gularso, Dhiniaty; Febrianto, Arip; Rahmawan, Andi Dian (Universitas Negeri Semarang, 2021)
It is important to educate children to inherit the ancestor’s tradition to maintain cultures as stated by Savira, A., Adefolake, A. M., Matsuo, M., Ito, M., Itoyama, R., Shiina, Y., Sok, S. (2018). The society of Balong Disctrict in Yogyakarta are struggling to preserve the cultures of their descendents through Kawruh Pamomong Ki Ageng Suryomentaram (to educate truthfully, passionately and beautifully) to their children. The purpose of this research is to reveal the medium or tool to educate the truth, passionate and beauty using Kawruh Pamomong Ki Ageng Suryomentaram to children in Balong District. This is a qualitative research by employing interview data, observation, documentation and forum group discussion. Data analysis employs Zamroni which consists of notice things, collect things and think about things. The result of this research indicates that mosque is used as a media to teach truth, passion and beauty to the children in Balong District. There are four periods of activities being conducted: 1) daily, the Qur’an Education Park in the afternoon at 3-5 p.m, 2) weekly, reading Yasiin every Friday evening, 3) monthly, the Selapanan, inviting ustadz or Islamic teacher once in 35 days, and 4) annual, the Muharram week, Ramadhan Activities, Idul Fitri Quranic Reading, Idul Adha activities, Isra’ Mi’raj, and Maulid the Prophet of Muhammad SAW.